MODELING THE DISPERSION OF TOTAL SUSPENDED SOLIDS (TSS) USING DELFT3D MODEL IN AKELAMO RIVER ESTUARY, SOUTH HALMAHERA REGENCY, NORTH MALUKU - Rizky Boary, Haryo
The river estuary is the location of the intersection of river water and sea water, which is a complex aquatic ecosystem. Human activities around water bodies can affect the quality of river water which in turn can affect the quality of waters in the estuary and coastal waters. One of the water quality parameters is the physical parameter in the form of total suspended solids (TSS). TSS can consist of organic, inorganic and sediment suspended in water bodies. The objective of this research is to create a simulation model that can describe the dispersion direction of TSS distribution from the river mouth to enter coastal waters. Model simulation was conducted using Delft3D hydrodynamic modelling software. The TSS test results were then used as model input and model validation and will be compared with the TSS quality standard value. Three simulation scenarios were created, namely 1000 mg/L, 154 mg/L and 5 mg/L TSS inputs that were run for 1 month (February 01 - February 28, 2023). Scenario 2 of the model was validated with day 1 TSS sample test results and scenario 3 of the model was validated with day 2 TSS sample test results. Model validation showed correlation values R2 = 0.3144 and 0.2968 and the values of RMSE = 12.151 mg/L and 55.673 mg/L. Model simulation results in the three scenarios showed that TSS distribution was not influenced by TSS concentration, but was influenced by tides and current velocity in coastal waters. The sampling results on February 20th, 2023 showed that the TSS distribution pattern moved to the north of the estuary at the highest tide with a current speed of 0.15 – 0.3 m/sec. While at the lowest ebb, the TSS distribution pattern moves towards the south of the estuary with a current speed of 0.3 – 0.5 m/sec. Comparison of TSS test results with quality standards showed that day 1 samples exceeded the Seawater Quality Standard (BMAL) and Class IV River Water Quality Standard, while day 2 samples met the BMAL for tourism and Class I River Water Quality Standard